Using the lens of liminality to understand important steps in creating conditions for networked learning in work-integrated learning - Lindqvist, Marcia Håkansson; Stockenstrand, Anna-Karin (Proceedings of the International Conference on Networked Learning, 2024)
In this paper university teachers’ and professionals’ work in the BUFFL project, a networked work-integrated lifelong learning project with flexible online course modules. The project involved a meeting space between academia and industry bank organizations or insurance companies in Sweden. Previous research in the project reported that four important steps are important for a successful establishment of a networked community of practice and networked learning. In this paper, the concept of liminality, or a liminal space, is used to explore work-integrated learning. The short paper concludes that there is a balance to strike between the risks and possibilities of liminality in learning in practice. From the different perspectives of liminality, a balance is needed when academia and industry meet. While both academia and industry bring their formal spaces and structures, this meeting can be said to create a liminal space that provides a free and uncertain place of possibilities where learning and transformation take place.